Analisis Peran Pemasaran Produk Syariah Dalam Mengoptimalkan Dana Pihak Ketiga Di Bank Syariah Indonesia Bojonegoro - Muhammad Husaini (Genius: Jurnal Ekonomi Dan Manajemen, 2024)
This study aims to determine and describe (1) marketing of sharia products at Bank Syariah Indonesia KC Bojonegoro, (2) third party funds at Sharia Indonesia KC Bojonegoro, (3) The effect of sharia product marketing on increasing third party funds at Sharia Indonesia KC Bojonegoro. In this study, sharia product marketing is an independent variable, while increasing third party funds is the dependent variable. This type of research uses quantitative research methods. While the data collection method uses interviews, documentation and questionnaires. Based on the results of data analysis, the results obtained that (1) marketing of sharia products at Bank Syariah Indonesia KC Bojonegoro is classified as very good, this is indicated by an average of 46.8 with an answer percentage value of 85%, where this value is between 81%-100% so it can be concluded that marketing of sharia products at Bank Syariah Indonesia KC Bojonegoro is very good, (2) third party funds at Sharia Indonesia KC Bojonegoro are very good, this is indicated by an average of 25,9 with an answer percentage value of 86% where this value is between 81%-100% so that it can be concluded that the marketing of Islamic products at Bank Syariah Indonesia KC Bojonegoro is very good, (3) The effect of marketing Islamic products on increasing third party funds at Sharia Indonesia KC Bojonegoro has a positive effect, this is indicated by the results of hypothesis testing that the value of tc> ttable or 3.299. t table or 3.299> 2.002 with a significance value < 5% significance level or 0.002 < 0.05, H0 is rejected and Ha is accepted, which means that there is a significant influence between marketing sharia products on increasing third party funds..